Teams Contribute More and Punish Less - Marcel Thum; Heike Auerswald; Carsten Schmidt; Gaute Torsvik (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
Many decisions in politics and business are made by teams rather than by single individuals. In contrast, economic models typically assume an individual rational decision maker. A rapidly growing body of (experimental) literature investigates team decisions in different settings. We study team decisions in a public goods contribution game with a costly punishment option and compare it to the behavior of individuals in a laboratory experiment. We also consider different team decision-making rules (unanimity, majority). We find that teams contribute significantly more and punish less than individuals, regardless of the team decision rule. Overall, teams yield higher payoffs than individuals.
Keywords: C72; C92; H41; 330